Clinical proof of concept for small molecule mediated inhibition of IL-17 in psoriasis - Richard B. Warren; Hamish J. A. Hunter; Kim A. Papp; Kenneth B. Gordon; Meina T. Tang; Jeffrey V. Enejosa; Kuan-Chieh Huang; Debasish Raha; Hashini M. Batugedara; Craig Skinner; Philip A. Kobel; Peter M. Rademacher; et al. (PLoS ONE, 2026)
Efficacious and well-tolerated systemic, oral treatments for psoriasis are needed. We report preclinical and phase 1c (NCT06808815) results for DC-806, a small molecule interleukin (IL)-17 inhibitor, for the treatment of mild-to-moderate psoriasis. Preclinical results demonstrated DC-806 targets IL-17AA and IL-17AF with secukinumab-like therapeutic efficacy. In the phase 1c trial, 32 patients consented to receive twice daily (BID) doses of placebo or DC-806 (200 mg or 800 mg) for 28 days. No serious adverse events (SAEs) or discontinuations due to treatment-related adverse events (TRAEs) occurred. In an exploratory analysis, adjusted mean percentage reductions from baseline in psoriasis area and severity indices (PASI) at Day 29 were 43.7%, 15.1%, and 13.3% for 800 mg BID, 200 mg BID, and placebo arms, respectively (800 mg BID vs placebo, P value = 0.0008). DC-806 was found to be well tolerated with an acceptable safety profile and preliminary signals of clinical efficacy in mild-to-moderate psoriasis. EudraCT Identifier: 2021-002888-21.